Burden of disease and impact on quality of life in chronic back pain – a comparative cross-sectional study of 150 axial spondyloarthritis and 150 orthopedic back pain patients - Frede, Natalie; Hiestand, Sonja; Endres, Dominique; van Elst, Ludger Tebartz; Finzel, Stephanie; Chevalier, Nina; Schramm, Markus A.; Rump, Ina C.; Thiel, Jens; Voll, Reinhard; Herget, Georg; Venhoff, Nils (Frontiers in Medicine, 2023)
Objective Chronic back pain (CBP) constitutes one of the most common complaints in primary care and a leading cause of disability worldwide. CBP may be of mechanical or inflammatory character and may lead to functional impairment and reduced quality of life. In this study, we aimed to assess and compare burden of disease, functional capacity, quality of life and depressive symptoms in axial spondyloarthritis (axSpA) patients with orthopedic chronic back pain patients (OBP). We further aimed to identify factors associated with quality of life. Methods Cross-sectional survey of a cohort of 300 CBP patients including 150 patients from a University Hospital Orthopedic Back Pain Outpatient Clinic with OBP and 150 patients with confirmed axSpA from a University Hospital Rheumatology Outpatient Clinic. Questionnaire-based assessment of pain character (Inflammatory Back Pain, MAIL-Scale), functional status (FFbH, BASFI), quality of life (WHOQOL-Bref) and depressive symptoms (Phq9) and retrospective medical chart analysis. Results Both, OBP and axSpA patients reported on average intermediate pain levels of mostly mixed pain character. Both groups demonstrated a reduced health-related quality of life and the presence of depressive symptoms. However, axSpA patients reported a significantly better subjective quality of life, more satisfaction with their health status and better functional capacity compared to OBP patients (all p < 0.001). In a multivariate regression model, depressive symptoms, mechanical back pain, pain level and age were negative predictors of subjective quality of life, whereas functional capacity was a positive predictor. Conclusion Chronic back pain was associated with a high morbidity and reduced quality of life regardless of pain character. We identified multiple factors associated with reduced quality of life. Awareness and addressing of these factors may help to overcome unmet needs and improve quality of life for these patients.